Alpha-gal Syndrome - A Case Report of Tick-Borne Anaphylactic Shock - Müller, Jiří; Radej, Jaroslav; Kriz, Miroslav; Huňková, Eliška; Kasparek, Jan; Matejovic, Martin (European journal of case reports in internal medicine, 2023)
UNLABELLED: The most common cause of vasoplegic shock in critical care is sepsis. However, although rarely and only in specifically sensitised individuals previously bitten by a tick, red meat may provoke a delayed allergic reaction called an alpha-gal syndrome. We present a case of a protracted life-threatening manifestation of alpha-gal syndrome, which, due to an unusual absence of typical features of anaphylaxis can masquerade as septic shock and calls attention to the premature diagnostic closure as a contributor to diagnostic error. Alpha-gal syndrome is a relatively new, but increasingly recognised health issue. We propose that alpha-gal syndrome should be considered in the differential diagnosis of vasoplegic shock of unclear aetiology even in the absence of typical allergic symptomatology and typical allergen exposure since alpha-gal is present in a wide variety of carriers. LEARNING POINTS: Alpha-gal syndrome, otherwise known as "red meat allergy", is a potentially life-threatening allergic syndrome induced by the immunological properties of tick saliva.A typical case of alpha-gal syndrome is a patient bitten by a tick who develops an allergic reaction, anaphylaxis or anaphylactic shock even after an ingestion of a significant amount of alpha-gal, typically present in red mammalian meat or organs.As global warming continues, we may expect tick-borne diseases to spread wider around the globe and due to the possibility of complete absence of typical allergic symptomatology and the delayed onset of symptoms, this syndrome needs to be considered when encountering vasoplegic shock of uncertain origin.